ZONASI KAWASAN RESAPAN AIR DAERAH CIJERUK, KECAMATAN CIJERUK, KABUPATEN BOGOR, PROVINSI JAWA BARAT: ZONATION OF WATER INSPECTION AREA IN CIJERUK REGION, CIJERUK DISTRICT, BOGOR REGENCY, WEST JAVA PROVINCE - Viona Dienty Paratin; Suherman Dwi Nuryana; Mohammad Apriniyadi (Journal of Geoscience Engineering & Energy (JOGEE), 2022)
Cijeruk known as a strategic location that is still very close to the Mount Salak area, but also close to the urban area of Bogor itself. This causes the area to have the potential to have good water absorption, but it also has the potential to be disturbed by water absorption due to internal and external factors in the research area. For this reason, it is necessary to know the water absorption and infiltration rate in order to see the advanced conditions of the research area. In order to know this, researchers need to obtain primary data by processing in the field using a Double Ring Infiltrometer (Indonesian National Standard, 7752:2012); while secondary data were obtained from previous researchers, as well as official bodies in Indonesia. The rainfall at the nearest Citeko station per 5 years reaches more than 3000mm, namely 3168.8mm, indicating that the research area has a very high potential for rainfall. In addition, it can be concluded that the research area has a type of overburden in the form of loamy sand with flat to steep areas in 4 observation locations, while the other 5 observation locations are flat to very steep. Then, the results obtained in the Cijeruk area obtained 2 units of infiltration rate, namely sufficient infiltration rate with an infiltration rate of 0.192 m/day to 0.312 m/day and a high infiltration rate with an infiltration rate of 1.08 m/day up to 5.04 m/day. indicates that the water catchment area is classified as good.